Diagnosing celiac disease in patients with a history of lymphoma: factors that matter - Balihar, Karel; Kozeluhova, Jana; Hejda, Vaclav; Krcma, Michal; Lysak, Daniel; Gorcikova, Jitka; Hes, Ondrej; Matejovic, Martin (Wiener klinische Wochenschrift, 2013)
OBJECTIVE: The aim of this study was to identify pitfalls in establishing the diagnosis of celiac disease (CD) in patients with a history of lymphoma. METHODS: A total of 103 patients with a history of lymphoma had anti-tissue transglutaminase antibodies (atTGA) and their class A, G, and M immunoglobulin (IgA, IgG) levels determined. Patients with atTGA positivity underwent enterobiopsy and CD-associated HLA locus testing. RESULTS: The mean age of patients was 55 ( ± 13.5) years. The predominant lymphoma types included B-type non-Hodgkin's lymphoma (B-NHL, 66 %), T-type NHL (8 %), and Hodgkin's lymphoma (26 %). Serological positivity was documented in 3.9 % of cases; one patient had the diagnosis of CD confirmed by enterobiopsy. In 11 patients (10.7 %), IgA levels were decreased to a various extent; of these patients, 10 were shown to have also their IgG levels decreased. The median time from follow-up to blood collection was 58 (32-104) months. The decrease in immunoglobulin levels correlated with a more advanced stage of the tumor (Ann Arbor III-IV) at the time of diagnosis [1.4 (0.9-2.0) g/l versus 2.4 (1.5-3.0) g/l for IgA, p = 0.0001; and 9.4 (7.2-11.5) g/l versus 11.2 (10.3-12.3) g/l for IgG, p = 0.001] and older age [65 (54-72) years versus 55 (44-61) years for IgA, p = 0.04; and 69 (59-74) years versus 53 (43-61) years for IgG, p = 0.0001]. Rituximab therapy in B-NHL patients had no effect on the subsequent incidence of decreased IgA levels. CONCLUSION: Reduced IgA and IgG levels represent important factors contributing to the low detection rate of serological screening for CD in patients with a history of lymphoma.
Keywords: Female; biologické markery; imunoglobulin G; Biomarkers; imunoglobulin A; ženské pohlaví; Reproducibility of Results; komorbidita; lidé; lymfom; Comorbidity; Immunoglobulin A; Sensitivity and Specificity; senzitivita a specificita; Immunoglobulin G; Humans; Risk Factors; Incidence; reprodukovatelnost výsledků; Lymphoma; Male; incidence; Czech Republic; rizikové faktory; Česká republika; Celiac Disease; lidé středního věku; mužské pohlaví; Middle Aged; celiakie; chybná diagnóza; Diagnostic Errors